Level shift device structure - ZHAO BO; WU WENJIE; ZHANG LINGFANG; JIN JIN (2024)
The invention provides a level shift device structure, which is characterized by comprising a level shift MOS (Metal Oxide Semiconductor) transistor positioned in a semiconductor region and comprising a source region, a drain region and a doped region; the isolation structure extends from the two sides of the doped region respectively so as to jointly form an annular closed shape, and the semiconductor region is divided into a high-voltage side region surrounded by the isolation structure and a low-voltage side region located on the periphery of the isolation structure; the drain electrode region is arranged in the high-voltage side region; and a source region disposed in the low voltage side region. The voltage resistance of the device is improved by setting the shape and the thickness of the isolation structure. 本发明提供一种电平移位器件结构，其特征在于，包括：位于一半导体区域内的电平移位MOS晶体管，包括源极区域，漏极区域和掺杂区域；隔离结构，从所述掺杂区域的两侧分别延伸，以共同呈环形闭合形状，将所述半导体区域划分为被所述隔离结构包围的高压侧区域，和位于所述隔离结构外围的低压侧区域；漏极区域，设置于所述高压侧区域中；以及源极区域，设置于所述低压侧区域中。本发明通过设置隔离结构的的形状和厚度以提高器件